Transformational Leadership sebagai Penggerak Kinerja Karyawan: Kajian Konseptual dalam Konteks Organisasi yang Dinamis - Joko Wiyono (FADZAT: Jurnal Ekonomi Syariah, 2025)
Rapidly changing business environments require leaders to adapt their leadership styles to remain relevant and effective. Transformational leadership (TL) has been proven to be one of the most significant leadership approaches in improving employee performance, but its effectiveness is highly dependent on the organizational context, particularly environmental dynamism. This study uses a conceptual qualitative approach to explore previous empirical findings, identify inconsistencies, and formulate a new theoretical model regarding the relationship between TL and employee performance. The synthesis of results indicates that TL influences performance through psychological, socio-organizational, and adaptive mechanisms, with psychological empowerment and organizational adaptability as mediators, and environmental dynamism as a moderator. This study makes an important conceptual contribution by extending classic TL theory through the integration of contextual factors relevant to modern organizations. Theoretical and practical implications are presented as a basis for further empirical research